2011
DOI: 10.1124/dmd.111.042259
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Absolute Protein Quantification of Transporters, Cytochromes P450, and UDP-Glucuronosyltransferases as a Novel Approach for the Characterization of Individual Human Liver: Comparison with mRNA Levels and Activities

Abstract: ABSTRACT:The purpose of the present study was to determine the absolute protein expression levels of multiple drug-metabolizing enzymes and transporters in 17 human liver biopsies, and to compare them with the mRNA expression levels and functional activities to evaluate the suitability of the three measures as parameters of hepatic metabolism. Absolute protein expression levels of 13 cytochrome P450 (P450) enzymes, NADPH-P450 reductase (P450R) and 6 UDPglucuronosyltransferase (UGT) enzymes in microsomal fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
380
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(430 citation statements)
references
References 35 publications
46
380
3
1
Order By: Relevance
“…Therefore, the effects of these changes may have minimal overall impact on RSV CL Bile . Available data suggest that expression of MRP3 and MRP4 in rat and human SCH may be relatively stable over days in culture (Swift et al, 2010a;Ohtsuki et al, 2012;Schaefer et al, 2012). However, robust quantitative proteomics data for transport proteins that mediate CL BL are not yet available.…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinmentioning
confidence: 99%
“…Therefore, the effects of these changes may have minimal overall impact on RSV CL Bile . Available data suggest that expression of MRP3 and MRP4 in rat and human SCH may be relatively stable over days in culture (Swift et al, 2010a;Ohtsuki et al, 2012;Schaefer et al, 2012). However, robust quantitative proteomics data for transport proteins that mediate CL BL are not yet available.…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinmentioning
confidence: 99%
“…Future studies should be designed such that they yield a clear definition and grading of posthepatectomy liver failure, which is currently not classified by a generally accepted scoring system (Rahbari et al, 2011). In all instances, future clinical studies should certainly involve longitudinal studies in individual patients, e.g., those listed for transplantation to overcome inherent limitations such as interindividual differences in transporter expression (Meier et al, 2006;Ohtsuki et al, 2011).…”
Section: Perspectivementioning
confidence: 99%
“…Several studies published recently reported different proteomic methodologies driven by advances in LC-MS technology (Fallon et al, 2008;Ohtsuki et al, 2012;Achour et al, 2014a;Vildhede et al, 2014;Harwood et al, 2015;Fallon et al, 2016). These methodologies focused on obtaining expression values from a range of mammalian tissues/organs (e.g., liver, intestine, kidneys) and in vitro systems (e.g., hepatocytes, Caco-2 cell lines), with a view to providing systems data for in vitro-in vivo extrapolation (IVIVE) of pharmacokinetic profiles using computerized physiologically based pharmacokinetic (PBPK) models (Rostami-Hodjegan, 2012;Bosgra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%